In situ DRIFTS investigation on the SCR of NO with NH3 over V2O5 catalyst supported by activated semi-coke - Wang, Jinping; Yan, Zheng; Liu, Lili; Chen, Yan; Zhang, Zuotai; Wang, Xidong (Applied surface science, 2014)
At the reaction temperature (200°C), the active sites for NO adsorption and oxidation are mostly provided by ASC and NH3 is mainly absorbed on the Lewis acid sites provided by V2O5. •High NO conversion rate with excellent selectivity to N2 is obtained when 3wt.% V2O5 is loaded onto ASC for NO removal.•Active sites for the adsorption–oxidation of NO and NH3 are proved to be respectively provided by ASC and V2O5.•Both Lewis and Brønsted acid sites for NH3 adsorption co-exist on the V2O5/ASC catalyst and the Lewis acid sites play the leading role at the reaction temperature.•The SCR reaction pathways over the V2O5/ASC catalyst involve the coordinated ammonia with gaseous NO (E–R mechanism) as well as the adsorbed NO2 (L–H mechanism). 3wt.% of V2O5 is loaded onto the activated semi-coke (V2O5/ASC) via impregnation method and used for low temperature selective catalytic reduction (SCR) of NOx with NH3. The prepared V2O5/ASC catalyst yields an over 90% NO conversion rate with excellent N2 selectivity at 250°C with a space velocity of 12,000h−1. The adsorption state of different species and reaction behaviors under various conditions are systematically examined with in situ diffuse reflectance infrared Fourier transform spectroscopy (in situ DRIFTS). It is evidenced that NH3 and NO are absorbed on different active sites over the V2O5/ASC catalyst. At the reaction temperature (200°C) in this study, NH3 is mainly absorbed on the Lewis acid sites provided by V2O5, and NO is mainly absorbed on the active sites originated from the support ASC. In addition, the NH3-SCR process takes place according to two pathways, including reaction between the coordinated NH3 and gaseous NO (E–R mechanism), and reaction between the absorbed NO2 and coordinated NH3 (L–H mechanism). The latter one plays a primary role for the improved low-temperature SCR performance of V2O5/ASC catalyst.